Water and sanitation hygiene practices among household members living in urban slum in Gwalior city: a cross sectional study - Sarswat, Swati; Saraswat, Satender (International Journal of Research in Medical Sciences, 2021)
Background: Population inhabit in urban slum of developing countries face sanitation, water supply and cleanliness related issues. We contemplated knowledge, attitudes and practices identified with drinking water and sanitation offices among urban slum populace of Gwalior city, Madhya Pradesh, India. Methods: It was a cross-sectional study comprising of individuals over 18 years of age residing at Muriya Pahar and Awadpura, Urban Slum, Gwalior (Madhya Pradesh) from September 2019 to December 2019. Total 120 individuals were interviewed using simple random sampling technique. Basic information about socio-demographic profile and existing drinking water and sanitation related knowledge, attitude, and practices was collected using a modified version of previously validated questionnaire and analysed. Results: Thirty five percent (35%) of the participants were following bleach/chlorine methods of water treatment while twenty five percent (25%) of the participants felt that water available to them was clean and did not require any additional treatment. Forty percent (40%) of the participants surveyed, did not have access to toilets inside their households. Conclusions: There is a requirement for mediation to instruct people about drinking water treatment techniques, sanitation, and hand washing rehearses.